The droplet size changes of 1% propofol before and after the storage procedure for 6 and 24 hours periods - Djayanti Sari, Basuki Rahmat Bambang Suryono S (Universitas Gadjah Mada, 2012)
Propofol (2,6-diisopropylphenol) is a popular anesthetic agent for induction and anestheticmaintenance. Propofol preparation is formulated as a lipid macroemulsion that is thermodynamicallyunstable and degraded over time, causing the enlargement of droplet size. The degradation is fasterwhen propofol emulsion preparation package has been opened. This droplet enlargement results indecreasing propofol releasing-rate and its concentration. The risk of embolism occurs whenever themean droplet size (MDS) exceeds Food and Drug Administration (FDA) limit (<0.45) and fat globulepopulation percentage >5 ïm (PFAT5) is <0.05%. In the daily practice, some propofol emulsionpreparation are often used although they are already opened and saved more than 24 hours. The aimof this study was to evaluate the droplet size changes of propofol emulsion preparation duringstorage. This was an observational study using cohort prospective design. The droplet size changesof sixteen propofol preparation samples were evaluated before and after storage procedure for 6 and24 hours in the refrigerator at the temperature of 4ÂºC. The droplet diameter was determined under alight microscope. Mean droplet size before and after storage were calculated and analyzed by oneway analysis of variance (ANOVA), followed by Tukeyâs post hoc test with 95% confidence interval(p<0.05). The droplet diameter of propofol emulsion preparation increased significantly (p<0.05)after storage procedure for 6 h (MDS value were: 247 Â± 22 nm) and 24 h (278 Â± 29 nm) comparedto before storage (225 Â± 24 nm). The PFAT5 at each interval time was 0%. There was no color andhomogeneity changing at each interval time (n=16/100% each time interval). In conclusion, there isa change of propofol emulsion preparation droplet size after storage procedure for 6 to 24 hours attemperature of 4ÂºC compared to before storage.